1987
DOI: 10.1177/000456328702400613
|View full text |Cite
|
Sign up to set email alerts
|

Blood Serotonin Levels in Adults, Autistic and Non-Autistic Children—With a Comparison of Different Methodologies

Abstract: SUMMARY.Recent interest in conditions associated with increased blood serotonin level has highlighted the need for consistency between assay methods to allow for more accurate delineation of serotinin variables. To this end, comparison was made between a spectrofluorimetric technique frequently used in the past and two potentially more specific high performance liquid chromatographic procedures. Normal ranges and diurnal variations for blood serotonin in adults, normal, autistic children and children with deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Blood 5-HT levels are generally stable in an individual over several months (Yuwiler et al 1970) and are not affected by ordinary changes in diet (Anderson et al 1984;Badcock et al 1987). An early study found that after acute loading with tryptophan, the precursor of 5-HT, changes in blood 5-HT levels were transient with a return to baseline levels within 8 h (Yuwiler et al 1981).…”
Section: Biochemical and Molecular Genetic Methodsmentioning
confidence: 99%
“…Blood 5-HT levels are generally stable in an individual over several months (Yuwiler et al 1970) and are not affected by ordinary changes in diet (Anderson et al 1984;Badcock et al 1987). An early study found that after acute loading with tryptophan, the precursor of 5-HT, changes in blood 5-HT levels were transient with a return to baseline levels within 8 h (Yuwiler et al 1981).…”
Section: Biochemical and Molecular Genetic Methodsmentioning
confidence: 99%
“…Laboratory studies suggest that individual differences in whole blood serotonin are stable over extended periods of a year or more (Badcock, Spence & Stern, 1987;Yuwiler, Brammer, Morley, Raleigh, Flannery, & Geller, 1981). Two previous clinical studies have shown that CSF serotonin indices can predict aggression and violence after two to three years of follow-up (Kruesi et aI., 1992;Virkkunen, Dejong, Bartko, Goodwin, & Linnoila, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Men and women were studied, to redress the dearth of studies of serotonin and violence among women . Factors known or suspected to influence concentrations of whole blood serotonin were examined, including use of psychiatric medication, ilIicit drugs or tobacco (Mann et aI., 1992), season of venipuncture Badcock, Spence & Stern, 1987;Brewerton et aI., 1988), blood platelet count (Ritvo, Yuwiler, Geller, Plotkin, Mason. & Saegar, 1971), and available precursor plasma tryptophan concentration (Chamberlain, Ervin, Pihl & Young, 1987;Fernstrom & Wurtman, 1971).…”
Section: Whole Blood Serotonin Relates To Violence In An Epidemiologimentioning
confidence: 99%
See 2 more Smart Citations